Murder capital : Suspicious deaths in London, 1933-53. - Bell, Amy Helen (Manchester University Press, 2016)
Murder capital is a historical study of unexpected deaths whose circumstances required official investigation in mid-twentieth-century London. Suspicious deaths - murders in the family and by strangers, infanticides and deaths from illegal abortions - reveal moments of personal and communal crisis in the social fabric of the city. The intimate details of these crimes revealed in police investigation files, newspaper reports and crime scene photographs hint at the fears and desires of people in London before, during and after the profound changes brought by the dislocations of the Second World.